265 DIFFERENT EXPRESSION OF ZINC TRANSPORTERS BETWEEN FETAL HUMAN (SMALL INTESTINE) (FHs) AND ADULT HUMAN INTESTINAL CELLS RESULTS IN DIVERGENT EFFECTS OF ZINC EXPOSURE. (1st January 2006) - Jou, M.; Kelleher, S. L.; Philipps, A.; Lonnerdal, B.
Abstract : Zinc (Zn) homeostasis in adults is primarily regulated by changes in intestine expression and localization of Zn-specific transporters such as Zip4 (primary Zn importer), ZnT-1 (Zn efflux), ZnT-2 (vesicular Zn sequestration), and MT-1 (intracellular metal-chelator). However, Zn absorption and excretion are higher and less regulated, respectively, in premature infants, suggesting that mechanism-regulating intestinal Zn homeostasis may be immature. We used cultured fetal (FHs) and adult (Caco-2) intestine cell lines to determine difference in Zn uptake, Zn transporter expression (MT-1, ZnT-1, ZnT-2, and Zip4), and effects of acute (1 h) Zn exposure (50 μM). Zn supplementation induced higher Zn uptake (3-fold) in fetal cells, which were also more sensitive to Zn exposure than adult cells (FHs, LD50 = 70 μM; Caco-2, LD50 = 120 μM). Our data suggest that these differences may be a result of differential expression of Zn-specific transporters as fetal cells do not express Zip4 but have higher Zip1 (2-fold) and Zip3 (3-fold) and lower ZnT-1 (20%) and ZnT-2 (50%) expression compared to adult cells. While acute Zn exposure post-transcriptionally increased Zip4 and ZnT-1 protein levels, resulting in no effects on MT-1 (an indicator of cellular stress or Zn levels) in adult cells, Zn exposure increased MT-1, ZnT-1, and ZnT-2 mRNA and ZnT-1 protein levels in fetal cells. We speculate that this difference is due to the inability of fetal cells to tightly regulate Zn uptake as a result of absence of Zip4 expression. In conclusion, our data suggest that the lack of Zip4 expression in fetal intestine cells may be responsible for the difference in Zn absorption observed between preterm infants and adults, resulting in the lack of sensitive regulation at this age.